Pendidikan Karakter Cinta Tanah Air Pada Anak Usia Dini - Katili, Sitti Nurul Afiah Koemaji; Sri Wahyuningsi Laiya; Yenti Juniarti (Student Journal of Early Childhood Education, 2024)
This research aims to describe how the character of love for one's country is formed through Strengthening Character Education activities at the Raudhatul Athfal AL-MOURKY School. The type of research used is a qualitative method with a descriptive approach. In this case, the main data are teachers and parents. The education of the character of love for the country in children is very good, many children listen to the advice given by teachers and are able to develop the character of love for the country within themselves. Based on research conducted at RA AL-MOURKY, Telaga District, Gorontalo Regency, the education of the character of love for the country in children is very good, many children listen to the advice given by teachers and are able to develop the character of love for the country in themselves. Teachers also build a harmonious atmosphere with children so that each child is united with each other, so that children do not develop feelings of discriminating against their friends.